INTRA AND EXTRABUCCAL ASPECTS OF MIXED VASCULAR MALFORMATION IN CHILDREN - Longo, Daniele Lucca; Oliveira, Fernanda Maria Machado Pereira Cabral de; Arnez, Maya Fernanda Manfrin; Martins, Giovana Gonçalves; de Queiroz, Alexandra Mussolino; Paula-Silva, Francisco Wanderley Garcia (Revista Uningá, 2021)
Vascular anomalies are disorders of endothelial cells that can affect capillaries, arteries, veins and / or the lymphatic system. They are classified as “vascular tumors” or “vascular malformations”. Vascular malformations are subdivided into capillary, lymphatic, venous, arteriovenous and mixed malformations according to the type of vessels affected. The aim of the present study is to report a case of a patient with mixed vascular malformation (veno-lymphatic) and to describe the dental planning and treatment carried out. Male patient, 7 years old, referred for dental evaluation. The mother reported that the patient was undergoing medical treatment at the hospital for presenting “hemangioma and lymphatic vascular malformation” in the oral region. During the clinical examination, veno-lymphatic vascular malformation was observed on the oral floor. The child reported difficulty in performing oral hygiene due to the injury, and several caries lesions were found. Dental treatment consisted of dental restorations, sealants and extraction of primary teeth. The treatment of mixed vascular malformation was performed with a sclerosing solution (OK-432). The oral health care of patients with vascular malformations should include oral hygiene instructions, supervised brushing and guidance on the use of soft brushes to avoid injury to the affected areas.